Kommerell's Diverticulum: An Unusual Cause of Chronic Cough. (20th November 2012) - Magazine, Rahul; Sambhaji, Charudutt; Shetty, Ranjan; Goneppanavar, Umesh
Abstract : A 62-year-old male presented to the outpatient department of chest with history of dry cough since two months and swelling on the anterior aspect of neck of 30-year duration. Physical examination revealed a goitre. However, further imaging studies revealed presence of another associated pathology, a Kommerell's diverticulum in association with a right aortic arch with aberrant left subclavian artery. The enlarged thyroid was not compressing the trachea, and its occurrence in this case could be incidental. The diverticulum was considered as the cause of chronic cough in our case as it was causing tracheal compression, and also there were no other obvious causes which could explain the symptom. Vascular anomalies such as Kommerell's diverticulum, though uncommon, should be considered in the differential diagnosis of chronic cough particularly when other common causes have been ruled out.